Eficacia del vendaje neuromuscular en distención del ligamento colateral interno a los deportistas que acuden al centro de fisioterapia de la Federación Deportiva de Chimborazo de la ciudad de riobamba en el período de enero a junio de 2015. - Fuenmayor Bonifáz, Danny Germán (2016)
The Kinesio Taping is a technique that globally has a great openness and acceptance by doctors and physiotherapists deportólogos those who preside over the use of this method, since its results to solve a numerous of diseases is very encouraging. In Ecuador it has now begun to occupy a significant space for health personnel who know the technique, although this is not the treatment of choice, which is why my research topic is focused on evaluating the effectiveness of pain relief when using neuromuscular bandage medial collateral ligament distention, patients who attended the physiotherapy center of the “Federación Deportiva de Chimborazo” Riobamba city in the period January to June 2015. The study of this technique focused on the assessment of pain using a scale to treat a population of 30 individuals dividing into two groups to apply the neuromuscular bandage to a group and other conventional treatment. The group presented better therapeutic results after five days of treatment was that to which you apply the Kinesio Taping as an adjunct treatment and established that 87 % of the population of this group had positive results. While to the conventional treatment group has 20% of patients with improvement, so statistically the group with the best results is the one who will apply the Kinesio Taping as an adjunct treatment and observed a benefit in improving patients and giving an excellent treatment expectation. Unlike the application of conventional treatment, which notes a longer recovery, obtaining a disinterest by the patient to treatment, succeeding in imposing his absence, so it is considered that the use of Kinesio Taping is an ideal choice for the best course of treatment.